If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(n + -2) = -6n + 25 Reorder the terms: 7(-2 + n) = -6n + 25 (-2 * 7 + n * 7) = -6n + 25 (-14 + 7n) = -6n + 25 Reorder the terms: -14 + 7n = 25 + -6n Solving -14 + 7n = 25 + -6n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '6n' to each side of the equation. -14 + 7n + 6n = 25 + -6n + 6n Combine like terms: 7n + 6n = 13n -14 + 13n = 25 + -6n + 6n Combine like terms: -6n + 6n = 0 -14 + 13n = 25 + 0 -14 + 13n = 25 Add '14' to each side of the equation. -14 + 14 + 13n = 25 + 14 Combine like terms: -14 + 14 = 0 0 + 13n = 25 + 14 13n = 25 + 14 Combine like terms: 25 + 14 = 39 13n = 39 Divide each side by '13'. n = 3 Simplifying n = 3
| -6+9(x-5)=14x+5-5x | | 58+x=156 | | 1+5r=6r+6 | | 3(x-2)(x+1)+(x+4)(x+2)=5(x-1)(x-1)-x-x+3(x-6) | | 15(x)=225 | | 2y+22=x | | 6x10/3 | | 12x^2+19x+6=0 | | 10+10j=76 | | 29+5n=8n+8(n+5) | | x=4tan | | 10(x+2)=26+14 | | 24x^4-18x^3=0 | | -2(n-3)=-4n+22 | | 4x-13=49 | | 8-5x=4x-19 | | Y-20=5 | | y=x^3-3x^2-45x+1 | | 5x-4=5x-4 | | 5m+2(m+6)=-2 | | -10+2n=n-4 | | 3(-3x-2)=-2x-4 | | 6x=-8x+6 | | 2x+10=2x-16 | | 6x-3+5x=5x+3 | | 2x+10=-9x-16 | | -3b^2+3b=-90 | | 8/11f=16 | | t^3-12t^2+36t-81=0 | | 12lnx=60 | | 9m+2m=55 | | -8x-2+7x=-9x-8 |